Deep Breathing Exercise in Improving Physical Changes in PulmonaryTuberculosis Patients - Muhamad Ihlasul Amal; Kusnanto Kusnanto; Tiyas Kusumaningrum (Universitas Airlangga, 2019)
Introduction: Pulmonary Tuberculosis is caused by Mycrobacterium Tuberculosis lead to lung parenchymal inflammation and reduce the total functional lung. Deep breathing exercises (DBE) is a pulmonary rehabilitation that can be used as an alternative method to maintain the lung function of patients with pulmonary tuberculosis.Methods: This study used a quasy experiments design. The population was all patients with pulmonary tuberculosis in Puskesmas Perak Timur Surabaya. The sample was selected using purposive sampling technique. DBE is the independent variable. The dependent variable were the physical changes include peak expiratoty flow rate (PEFR), oxygen saturation, respiratory rate (RR), breath sounds, and dyspnea. Data was collected by observation tools (pulse oximetry, peak flow meters). Data was analyzed using Independent T-test, Paired T-test, Chi Square, and McNemar.Results: The results showed a significant change in breath sounds (p=0,031) and dyspnea (p=0.031) after given DBE, but no significant difference in PEFR (p=0.155), oxygen saturation (p=0,730) and respiratory rate (p=0.125) after given DBE.Conclusions: Nurses can use the DBE as respiratory management intervention in patients with pulmonary tuberculosis and as a basis for making SOP DBE in patients with pulmonary tuberculosis.